Combusted molluscs shell as solid base catalyst for transesterification to produce biodiesel in an ultrasonic field / Dayang Aisah Abang Chi, Norhasnan Sahari and Rabuyah Ni - Abang Chi, Dayang Aisah; Sahari, Norhasnan; Ni, Rabuyah (UITM Sarawak,Kampus Samarahan, 2016)
The production of biodiesel can significantly reduce harmful emissions and contributing to domestic energy security (Eevera et al., 2009). For the production of biodiesel, triglycerides, the major component of vegetable oils undergoes transesterification with alcohol to form esters in basic conditions(Van Gerpen et al., 2004).However, (Kouzu et al., 2008) suggest that the common base used for such reaction such as potassium hydroxide (KOH) and sodium hydroxide (NaOH) can lead to massive wastewater discharge to wash the dissolved alkali-hydroxide. They suggest the use of calcium oxide (CaO) which is milder. Although the transesterification reaction rate of CaO is lower than KOH and NaOH, the catalytic activity can be improved by calcination process(Granados et al., 2007). Ultrasonic energy can also improve transesterification reaction using CaO as catalyst (Stavarache et al., 2005). It was also reported that ultrasonic field can accelerate transesterification reaction due to effective emulsification compared to the conventional mechanical stirring condition(Hanh et al., 2009). This is because ultrasonic irradiation can produce emulsions of immiscible liquids thus increasing the reaction area(Mason & Phillip, 2002). In Malaysia, the shellfish industry flourish with the support of the government and it was estimated that the industry to produce 130 000 tons per year mainly in the form of cockles (Sulaiman K., 2007). With that estimation, the problem for shell disposal can be predicted. The need to dispose of mollucs shells from the food industry namely oyster shell lead to researchers to investigate its usage as transesterification catalyst for biodiesel production (Nakatani et al., 2009). Molluscs shell such as oyster and cockles also have high content of calcite(Yoon et al., 2003). Thus, calcium oxides can be produced from combusted molluscs shell (Nakatani et al., 2009). Commercially available calcium oxides are usually produced from combusted calcium carbonate stones.